Of courtiers and kings: the biblical Daniel narratives and ancient story-collections - Holm, Tawny L. (Explorations in ancient Near Eastern civilizations, 2013)
Intro -- Preface -- Abbreviations -- Introduction -- The Story-Collection Genre: Survey and Prospect -- 2.1. Defining the Genre -- 2.2. Basic Characteristics of the Story-Collection -- 2.2.1. Complex and Compound Nature -- 2.2.2. Structure: Diversity and Coherence -- 2.2.3. Function: Instruction vs. Entertainment -- 2.2.4. Orality and Literariness: The Interaction between Oral Performance and Written Composition -- 2.2.5. Popular Nature -- 2.3. Literary Processes: Composition and Textual History -- 2.3.1. Selection of Material -- 2.3.2. Sources and Analogues -- 2.3.3. Duplicate stories -- 2.3.4. Open-endedness -- 2.3.5. Non-fixity or Indeterminacy of Text -- 2.4. Prospect for Daniel -- The Story-Collection and Related Material in Antiquity -- 3.1. Greece and Rome -- 3.1.1. Greece -- 3.1.1.1. The Fables and Life of Aesop -- 3.1.1.2. The Aetia of Callimachus -- 3.1.2. Rome -- 3.1.3. Summary of Classical Story-Collections -- 3.2. India and Persia -- 3.3. The Near East and Egypt -- 3.3.1. The Ancient Near East -- 3.3.1.1. Hurrian-Hittite Fable Collection -- 3.3.1.2. Mesopotamia -- 3.3.1.3. Northwest Semitic -- 3.3.2. Egypt -- 3.3.2.1. Use of the Frame Narrative -- 3.3.2.2. Egyptian Magicians: Priestly Sages and Court Scholars -- 3.3.2.3. Egyptian Story-Collections -- 3.3.2.4. Egyptian Court Tales and Cycles of Court Tales -- 3.3.2.5. Conclusions about Egyptian Story-Collections and Court Tales -- 3.4. Summary -- The Book of Daniel in Light of the Story-Collection Genre -- 4.1. The Story-Collection Definition and Daniel 1-6 -- 4.1.1. Basic characteristics of the story-collection -- 4.1.1.1. Genre: Daniel 1-6 and the Court Tale -- Excursus: The Genre of the Additional Stories in Greek -- 4.1.1.2. Transformation of Genre: The Relationship of the Stories to Each Other and to the Visions -- 4.1.2. Function: Instruction v. Entertainment in Daniel.